The Effect of Social Support on Relationship Quality and Social Commerce Intention - Evi Noviaty (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2026)
In the era of social commerce, individuals share their knowledge, experiences, and information about products and services with people in their neighborhoods or close friends. Based on social support theory, relationship quality, and social media concepts, this study proposes a model that aims to investigate more deeply the role of social factors influencing relationship quality—comprising commitment, trust, and satisfaction—as well as social commerce intention. Data were collected through online surveys and questionnaires distributed via the most popular social networking sites in Indonesia. The proposed model was empirically tested using the PLS-SEM method. The results indicate that social factors have a significant influence on relationship quality and social commerce intention. This study highlights changes in consumer behavior in the era of social commerce and contributes to the development of theory in the social commerce context. Practically, the findings suggest that technological changes in e-commerce present both new opportunities and challenges for practitioners to adapt and effectively leverage these developments.